Serious Impact of Handlebar Injuries. (June 2014) - Cherniawsky, Hannah; Bratu, Ioana; Rankin, Tara; Sevcik, William (Bill)
Background . Injuries from bicycles is a leading cause of trauma in children. We sought to investigate the epidemiology of bicycle handlebar injuries. Methods . A retrospective analysis of bicycle trauma treated at our institution was preformed. Results . A total of 462 children younger than 17 years had bicycle trauma. Abdominal handlebar injuries, representing 9% of bicycle injuries, contributed to 19% of all internal organ injuries, and 45.4% of solid, 87.5% of hollow, 66.6% of vascular or lymphatic, and 100% of pancreatic injuries. Handlebar injuries were 10 times more likely to cause severe injury, yet more than half of the children were misdiagnosed at their initial presentation. Delayed diagnosis and longer hospital stays were observed in handlebar injuries to the abdomen. Conclusion . Physicians should be aware of the serious impact of bicycle handlebar injury to the abdomen. The mechanism alone should raise the suspicion of internal organ injury, and timely imaging and surgical consultation.